Internet use among young people with and without mental health difficulties. (2nd November 2016) - Mullen, G.; Dowling, C.; O'Reilly, G.
Abstract : Objectives: Research regarding adolescent internet use and mental health is sparse. However, awareness of a young person's internet use is becoming increasingly recognised as an important element of clinical assessment and intervention, and requires the development of an evidence base. The aim of the present study was to better understand the internet use of young people experiencing mental health difficulties and to contrast it with those who currently report no concerns. Method: In total, 299 young people aged 12–19 years, across a continuum of mental health difficulties, completed an online survey measuring internet use and related experiences. Young people were assigned to four groups: (a) attending inpatient services; (b) attending outpatient services; (c) a community group with mental health concerns and no clinical support; and (d) a regular community group. Results: Those in the inpatient and outpatient groups visited more potentially harmful websites. Young people attending inpatient and outpatient services showed aspects of both more risky and less risky use. The community group reporting no mental health difficulties showed least risky use. The group experiencing difficulties but not receiving support showed consistently high risky use, suggesting this is a particularly vulnerable group. Conclusions: Despite methodological limitations, findings suggest that those with mental health difficulties may experience more of the risks and fewer of the benefits offered by the internet. Though further research is needed to clarify these findings, clinicians should consider routine assessment of Internet use when planning interventions for young people experiencing mental health difficulties.